Bridge to Terabithia - Paterson, Katherine; Diamond, Donna (New York : Scholastic, 1995)
Fifth grader Jess Aarons, a ten-year-old boy in rural Virginia, becomes friends with Leslie Burke, a newcomer who subsequently meets an untimely death trying to reach their magical kingdom in the woods, Terabithia, during a storm.
Includes "Literature circle questions," activities, and bibliography of the author's other novels: p. [129-130]
"This edition is only available for distribution through the school market."-- Back cover.
Cover c. 1995, HarperCollins.
Newbery Medal, 1978.
Keywords: Friendship -- Juvenile fiction; Death -- Juvenile fiction